A few days ago
nghlife

# Solve 6×2 + 3x – 18 = 0 using the quadratic formula.?

Solve 6×2 + 3x – 18 = 0 using the quadratic formula.?

A few days ago
helper

(-3+/-suare root(3^2-4(6)(-18)))/(2(6))

=(-3+/-21)/12

The two solutions are -24/12=-2 and 18/12=1.5

0

4 years ago
?
6×2 + 3x – 18 = 0 Divide for the era of by technique of three, we get: 2x^2 + x – 6 = 0 answer utilizing formula: For a quadratic equation ax^2 + bx + c = 0, we’ve 2 recommendations x1 and x2 such that: x1 = (-b + sqrt(b^2 – 4ac)) / 2a x2 = (-b – sqrt(b^2 – 4ac)) / 2a For the given equation, a=2, b=a million, c=-6 x1 = (-a million + sqrt(a million^2 – 4(2)(-6))) / 2*2 = (-a million + sqrt(a million + 40 8)) / 4 = (-a million + sqrt(40 9)) / 4 = (-a million + 7) / 4 = 6/4 = 3/2 in addition, x2 = (-a million – sqrt(a million^2 – 4(2)(-6))) / 2*2 = (-a million – sqrt(a million + 40 8)) / 4 = (-a million – sqrt(40 9)) / 4 = (-a million – 7)/4 = -8/4 =-2 So, x=-2 or 3/2 … ans wish this helps.
0

A few days ago
Anonymous
divide the equation by 3

:2×2+x-6

(2x-3)(x+2)

2x-3=0 x+2=0

x=3/2 x=-2

0